A Novel Approach of Manufacturing Sustainable Seamless Jute Bags and Evaluation of Its Properties: A Comparative Study with Commercial Bags - Shah Alimuzzaman; Md. Reasat Aktar Arin; Md. Abdullah Al. Mamun; A. N. M. Masudur Rahman; Md. Reajul Islam (Journal of Natural Fibers)
To reduce the adverse impact of synthetic bags on carbon footprints, greenhouse gases, and global warming, there is a rising demand for biodegradable and sustainable packaging material, especially for packing crops and food. Bags made from natural fibers are the finest alternative to synthetic ones. Jute is one of the most in-demand natural fibers in the packaging industry. Nevertheless, the traditional production method is more process-oriented, requiring more time and resulting in more expensive bags. Bowing problems induced by side seams cause sack bundles to roll during transport, which is also another issue. This study describes a unique process for producing seamless jute bags and sacks, eliminating the current processes in favor of fewer processes. A mechanical left-handed dobby loom with a cutting arrangement for separating the sacks produced continuous sack weaving. The tensile and seam strength of the produced sacks were evaluated and found to be comparable to those of commercially available sacks. In addition, one-way ANOVA and regression studies demonstrated the results significance. This developed method will increase productivity while reducing energy consumption, resulting in inexpensive packaging products and a solution to the transportation issue.